Functional Architecture of Deleterious Genetic Variants in the Genome of a Wrangel Island Mammoth - Fry, Erin (Genome Biol Evol, 2020)
Woolly mammoths were among the most abundant cold-adapted species during the Pleistocene. Their once-large populations went extinct in two waves, an end-Pleistocene extinction of continental populations followed by the mid-Holocene extinction of relict populations on St. Paul Island ∼5,600 years ago and Wrangel Island ∼4,000 years ago. Wrangel Island mammoths experienced an episode of rapid demographic decline coincident with their isolation, leading to a small population, reduced genetic diversity, and the fixation of putatively deleterious alleles, but the functional consequences of these processes are unclear. Here, we show that a Wrangel Island mammoth genome had many putative deleterious mutations that are predicted to cause diverse behavioral and developmental defects. Resurrection and functional characterization of several genes from the Wrangel Island mammoth carrying putatively deleterious substitutions identified both loss and gain of function mutations in genes associated with developmental defects (HYLS1), oligozoospermia and reduced male fertility (NKD1), diabetes (NEUROG3), and the ability to detect floral scents (OR5A1). These data suggest that at least one Wrangel Island mammoth may have suffered adverse consequences from reduced population size and isolation.